Légendaire et toponymie : la Table de Roland: nom primitif du mont Sainte-Anne dans la région de Percé - Poirier, Jean (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1981)
AbstractToponymics, like ethnology, is a fieldwork science. But when the names that are the subject of study are buried as long in time and legend as that of Mount Rolland in the Gaspé (for which one of the early names was Roland's Table), the study also involves history. For the mountain's former name, which has puzzled placename scholars, the author here proposes an explanation which reconciles legend with history.